Thymoquinone-loaded nanostructured lipid carrier reduces proliferation of human liver cancer cells, HepG2 - Mustafa Azmy, Nurfahima; Haron, Aminah Suhaila; Syed Alwi, Sharifah Sakinah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Hepatocellular carcinoma is one of the most common cancers that affected human in more than half of the world population. Although there is yet any alternatives treatment found for this disease, the antitumor property of thymoquinone has been well studied in most of cancer cell lines. Nonetheless, poor bioavailability of TQ limits its efficiency. The encapsulation form of TQ, TQ-NLC is suggested to enhance its bioavailability as well as cytotoxicity towards cancer cells via increasing resistance time and targeting drug to specified location in the body. Therefore, it is a great advantage to look at the effects of TQ-NLC towards HepG2. This study is design to look at the anti-proliferative effect of TQ-NLC on HepG2 and the changes in the cells morphology. Methods: Both cells were bought from ATCC and cultured in supplemented DMEM. Cell viability was determined via MTT assay. Pro-apoptotic effect of TQ-NLC was further confirmed with Annexin V staining. Morphology hallmarks of apoptosis of treated cells were also analysed using inverted microscope. Images were captured at 24, 48 and 72 hours. Results: TQ-NLC was very potent towards HepG2 compared to 3T3 with the relative IC50 of 25 μM. TQ-NLC was also more potent compared to the non-encapsulated form, TQ. Further analysis confirmed that TQ-NLC capable to increase the percentage of apoptotic cells in time-dependent manner. Qualitatively, all treated cells displayed the apoptosis morphology with increasing concentration and longer time-point. Conclusion: TQ-NLC showed greater cytotoxic effects towards HepG2 which was further confirmed with the morphological analysis.